Intravenous antiplatelet therapy with cangrelor vs. tirofiban in patients with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention. (3rd October 2022) - Centore, M; Silverio, A; Scudiero, F; Di Maio, M; Muraca, I; Dossi, F; Petrini, F; Brenca, D; Maiellaro, F; Attisano, T; Parodi, G; Musumeci, G; et al.
Abstract: Background: Intravenous antiplatelet drugs provide rapid and sustained inhibition of platelet aggregation and can mitigate the ischemic risk of patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (pPCI). However, there are few real-world studies comparing cangrelor to tirofiban in this patient population. Purpose: The aim of this study was to evaluate the effectiveness and the safety of cangrelor compared to tirofiban in a real-world population of STEMI patients undergoing pPCI. Methods: This was a prospective, multicenter, observational study including consecutive STEMI patients who received either cangrelor or tirofiban during pPCI at six Italian high-volume pPCI centers from January 2020 to January 2022. The study population was divided into two groups according the antiplatelet treatment received (cangrelor or tirofiban). The primary study outcome was impaired myocardial revascularization assessed by post-procedural Thrombolysis in Myocardial Infarction (TIMI) flow grade <3. The secondary outcome measures were major bleeding, defined as Bleeding Academic Research Consortium (BARC) type 3 or 5, and all-cause mortality during the hospitalization. Results: A total of 478 STEMI patients received intravenous antiplatelet therapy during pPCI. Of them, 16 patients were excluded since they received both cangrelor and tirofiban as bailout strategy. Thus, the final study population included 462 patients (mean age 63.9±11.8 years; 79.7% males): 223 patients received cangrelor (48.3%), and 239 tirofiban (51.7%). Patients treated with tirofiban had higher prevalence of prior myocardial infarction (p=0.016) and prior PCI (p=0.048) than patients receiving cangrelor (Table 1); also, they showed higher SYNTAX score (p=0.038) than patients receiving cangrelor, and a higher proportion of stent thrombosis as culprit lesion (p=0.047; Table 2). Conversely, patients treated with cangrelor had worse Killip class (p<0.001), and underwent more frequently pPCI via femoral access. Post-procedural TIMI flow<3 was reported in 114 (24.7%) patients. At propensity score adjusted regression analysis, the use of cangrelor was associated with a lower probability of post-procedural TIMI flow<3 (aOR: 0.530; 95% CI: 0.313–0.900; p=0.019) than tirofiban. Major bleeding and all-cause death occurred in 28 (6.1%) and 19 (4.1%) patients. There was no difference in the risk of major bleeding (aOR: 1.626; 95% CI: 0.618–4.279; p=0.324) and death (aOR: 2.724; 95% CI: 0.719–10.318; p=0.140) between groups. Conclusions: In this real-world population of STEMI patients undergoing pPCI, periprocedural use of cangrelor was associated with improved myocardial reperfusion compared to tirofiban, but with no differences in terms of major bleeding or death during the hospitalization. Funding Acknowledgement: Type of funding sources: None.